Understanding the Antecedents of MNC'S Performance: An Empirical Analysis - Loo, Yew Liang (2011)
This study was conducted to explore the influences which consist of knowledge sharing, local subsidiary's top management compensation system, local subsidiary top manager's role, and cultural difference on multinational corporation's (MNC's) performance. These influences were treated as independent variables and MNC's performance was treated as dependent variables respectively. This study was focused on the identified influences effects in MNC's performance to examine its performance among the employees between headquarters and subsidiary. Data was collected through the distribution of questionnaires which was designed to measure the MNC's performance with a statement on a five likert scale point then ranging from one (strongly disagree) to five (strongly agree). Four hypotheses were tested for this study. Data was analyzed by using the Statistical Package for Social Science (SPSS) software to obtain the frequencies, reliability, correlations, and linear regression between variables. The results show that four independent variables have positive relationship with MNC's performance. Thus, knowledge sharing, local subsidiary's top management compensation system, local subsidiary top manager's role, and cultural difference are obviously critical to MNC's performance and future research is essential in order to help the organization to increase their competitiveness in international arena or globally compete to each others.